PENGENDALI LAMPU RUMAH BERBASIS ESP8266 DENGAN PROTOKOL MQTT - Rizki Priya Pratama (Universitas Tarumanagara, 2020)
The smart home is a system that provides comfort, safety, and energy savings, automatically. This system can be used to control electrical equipment such as lights, water pumps, air conditioners, etc. By replacing any conventional switch into a wireless switch, users can control this device from inside and outside the home automatically. The design of this lamp controller uses the ESP8266 module, relay driver, Tenstar Robot SMPS power supply, and TTP223 touch sensor. This control device is made as small as possible so that it can fit into inbow dus switch. The ESP8266 programming platform is Arduino by implementing the PubSubClient library for communication on the MQTT protocol. With the MQTT protocol, the system is created by giving orders via the topic